Lives of literature : reading, teaching, knowing - Weinstein, Arnold (UK : Princeton University Press, 2021)
"Mixing passion and humor, a personal work of literary criticism that demonstrates the power of our greatest books to illuminate our lives. Why do we read literature? For Arnold Weinstein, the answer is clear: literature allows us to become someone else. Literature changes us by giving us intimate access to an astonishing variety of other lives, experiences, and places across the ages. Reflecting on a lifetime of reading, teaching, and writing, The Lives of Literature explores, with passion, humor, and whirring intellect, a professor's life, the thrills and traps of teaching, and, most of all, the power of literature to lead us to a deeper understanding of ourselves and the worlds we inhabit. As an identical twin, Weinstein experienced early the dislocation of being mistaken for another person--and of feeling that he might be someone other than he had thought. In vivid readings elucidating the classics of authors ranging from Sophocles to James Joyce and Toni Morrison, he explores what we learn by identifying with their protagonists, including those who, undone by wreckage and loss, discover that all their beliefs are illusions. Weinstein masterfully argues that literature's knowing differs entirely from what one ends up knowing when studying mathematics or physics or even history: by entering these characters' lives, readers acquire a unique form of knowledge--and come to understand its cost. In The Lives of Literature, a master writer and teacher shares his love of the books that he has taught and been taught by, showing us that literature matters most because we never stop discovering who we are"--
Includes bibliographical references and index.
Keywords: Weinstein, Arnold -- Books and reading; Literature -- Philosophy; Characters and characteristics in literature; Self in literature; Best books; LITERARY CRITICISM / General; LITERARY CRITICISM / Semiotics & Theory; Literary criticism